Nobeyama 45 m mapping observations toward the nearby molecular clouds Orion A, Aquila Rift, and M17: Project overview. (6th September 2019) - Nakamura, Fumitaka; Ishii, Shun; Dobashi, Kazuhito; Shimoikura, Tomomi; Shimajiri, Yoshito; Kawabe, Ryohei; Tanabe, Yoshihiro; Hirose, Asha; Oyamada, Shuri; Urasawa, Yumiko; Takemura, Hideaki; Tsukagoshi, Takashi; et al.
Abstract: We carried out mapping observations toward three nearby molecular clouds, Orion A, Aquila Rift, and M 17, using a new 100 GHz receiver, FOREST, on the Nobeyama 45 m telescope. We describe the details of the data obtained such as intensity calibration, data sensitivity, angular resolution, and velocity resolution. Each target contains at least one high-mass star-forming region. The target molecular lines were 12 CO ( J = 1–0), 13 CO ( J = 1–0), C 18 O ( J = 1–0), N2 H + ( J = 1–0), and CCS ( JN = 87 –76 ), with which we covered the density range of 10 2 cm −3 to 10 6 cm −3 with an angular resolution of ∼20″ and a velocity resolution of ∼0.1 km s −1 . Assuming the representative distances of 414 pc, 436 pc, and 2.1 kpc, the maps of Orion A, Aquila Rift, and M17 cover most of the densest parts with areas of about 7 pc × 15 pc, 7 pc × 7 pc, and 36 pc × 18 pc, respectively. On the basis of the 13 CO column density distribution, the total molecular masses are derived to be 3.86 × 10^4 M_, 2.67 × 10^4 M_, and 8.1× 10^5 M_ for Orion A, Aquila Rift, and M17, respectively. For all the clouds, the H2 column density exceeds the theoretical threshold for high-mass star formation of ≳ 1 g cm −2 only toward the regions which contain current high-mass star-forming sites. For other areas, further mass accretion or dynamical compression would be necessary for future high-mass star formation. This is consistent with the current star formation activity. Using the 12 CO data, we demonstrate that our data have enough capability to identify molecular outflows, and for the Aquila Rift we identify four new outflow candidates. The scientific results will be discussed in detail in separate papers.